Factores productivos y económicos de la panela en la parroquia Pucayacu, Cotopaxi. - López Vidal, Kevin Leonel (2022)
Panela craft is one of the categories with the greatest tradition in the highlands of ecuador, especially in the rural parish Pucayacu, belonging to the province of Cotopaxi, where they produce two types of sugar cane, organic and conventional, in two presentations in block and grainy, where the main actors are unaware of the impacts that their productions, whose situation is a limitation of development, for reasons cited above, the purpose of research is to determine the factors of production and economic of the panela in the parish Pucayacu, Cotopaxi. For the obtaining of results, study methodologies were used, for the analysis of the production systems of organic and conventional panela, the Hernández methodology was used, which allowed to develop a survey with socioeconomic and agro-productive variables; to set economic indicators of the systems of production of sugar cane were applied to four methodologies the Crow, which classified the costs into fixed and variable, Mendoza determined unit costs are so many variables and fixed, for the calculation of cost-effectiveness is applied to the Cohen and Franco, via the indicator of Johnston and Madrigal are determinò the point of balance; to make the proposal of organic certification is performed through the steps of obtaining organic certification in Ecuador, the institution Kiwa BCS. Within the results, it was established that 83.33% of producers produce organic panela, actors that are associated with an organization that provide them benefits in their production, the organic panela presents greater profitability in its two presentations, granulated with an average profitability index of 30.33%, in block 9.67%. The organic certification plan provides new development alternatives, which will allow them to market their products in a transparent and timely manner in local, national and international markets.